Asteraceae do Parque Estadual do Biribiri, Diamantina, Minas Gerais: Barnadesieae, Mutisieae sensu lato, Astereae e Senecioneae - Franco, Izabela Moreira (2014)
CHAPTER I: The study of the tribes Barnadesieae and Mutisieae sensu lato is part of a floristic survey of Asteraceae, in Biribiri State Park, Diamantina, Minas Gerais, Brazil. The study area is located in the Diamantina Plateau, central portion of the Espinhaço Range in Minas Gerais State, a place with a great specific diversity and a high degree of endemism, but with few flora published. A total of 12 field expeditions was carried out, between August/2011 and August/2013. The Barnadesieae tribe is represented by the genus Dasyphyllum, with three species. The Mutisieae sensu lato tribe is represented by five genera: Chaptalia (3 spp.), Moquiniastrum (4 spp.) Richterago (6 spp.), Trixis (2 spp.), and Wunderlichia (2spp.). This study presents a sistematic treatment of these basal grades of Asteraceae, with descriptions, identification keys and comments about geographical distribution. CHAPTER II: The treatment of the tribes Astereae and Senecioneae is part of a floristc survey realized with the botanic family Asteraceae, in the Biribiri State Park, Diamantina, Minas Gerais, Brazil. The study area is located in the Diamantina Plateau, central portion of the Espinhaço Range in Minas Gerais State, a region with a great diversity, a high degree of endemism, but with few flora surveys realized with the Asteraceae family so far. A total of 12 field expeditions were conducted, between August/2011 and August/2013. Some herbarium material collected in the Statual Park was also consulted. The Astereae tribe is represented by 12 species of the genus Baccharis L. The Senecioneae tribe is represented by six species from four genus: Emilia Cass. (1 sp.), Erechtites Raf. (1 sp.), Hoehnephytum Cabrera (1 sp.), and Senecio L. (3 spp.). This study presents a sistematic treatment of these two tribes of Asteraceae, with descriptions, identification keys, comments about geographical distribution, taxonomic affinities and photograps of the species.